Diseño de ingeniería básica de una línea de producción para el aprovechamiento de vísceras rojas de porcino del cantón Rumiñahui, Pichincha - Escobar Humaquinga, Christian Daniel (2017)
In Ecuador, there is a high consumption of pork that represents 11kg per year in 2013, therefore a large production of viscera, which its nutritional composition could help with important nutrients for human consumption, however due to ignorance or short life of untreated viscera, they are usually destined for the elaboration of food for animals and only a small part is consumed, mainly in typical dishes. Therefore, it is evident the little use of a raw material with high commercial potential. Ruminahui Canton is known for its high pork production and for the sale of its gastronomic referent, "hornado". So there is high generation of viscera in the area that could be used in a better way. This work presents a proposal for basic engineering design of a production line for using of red viscera (heart, liver and kidneys) of pigs in Ruminahui canton. To do this, historical production data of viscera in the country and in Ruminahui Canton were analyzed, for which the records of the Municipal Camal that was closed in the year 2012 were taken into account; in which 2.244 pigs were slaughtered 12 months before closing. The proposal of the line of exploitation will be introduced in a ground of 447 m2. The design was based on municipal ordinances, INEN norms for the management of these products, standards established by the Ministry of Agriculture, Fisheries and Aquaculture MAGAP, rules of construction for slaughterhouses and BPMs. For this project, an investment of USD68,296.16 is needed and the value of fixed and variable costs is USD175,988.33. A fourth scale product was estimated in a PSP of USD2.00 per 800 gr, resulting in an ROE of USD0.64 per dollar invested and a ROI of USD0.99, which indicates that it is a profitable project, without neglecting the social benefits that the generation and dynamization of agroindustrial activities that are gotten in the area, contributing to boost the economy of the area and promoting the quality and safety of food.